2018
DOI: 10.1007/s10803-018-3605-y
|View full text |Cite|
|
Sign up to set email alerts
|

The Association Between Emotional and Behavioral Problems in Children with Autism Spectrum Disorder and Psychological Distress in Their Parents: A Systematic Review and Meta-analysis

Abstract: This review (Prospero Registration Number: CRD42017057915) aimed to systematically identify and summarize existing research on the relationship between additional emotional and behavioral problems (EBP) in children with autism, and parenting stress (PS) and mental health problems (MHP) in their parents. Sixty-seven studies met criteria for inclusion in the review, 61 of which were included in the meta-analysis. Pooled correlation coefficients were in the low to moderate range (). Some evidence for moderation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
109
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 187 publications
(148 citation statements)
references
References 108 publications
(191 reference statements)
17
109
0
5
Order By: Relevance
“…Because both anxiety and ADHD are common in children with ASD, and may underlie disruptive behavior, it is important to assess the effects of intervention on these domains of EBPs. Furthermore, parental functioning and well-being outcomes are important as they are also commonly impaired in families with a child with ASD (Estes et al, 2013), and could also be related to long-term child well-being outcomes (Yorke et al, 2018).…”
mentioning
confidence: 99%
“…Because both anxiety and ADHD are common in children with ASD, and may underlie disruptive behavior, it is important to assess the effects of intervention on these domains of EBPs. Furthermore, parental functioning and well-being outcomes are important as they are also commonly impaired in families with a child with ASD (Estes et al, 2013), and could also be related to long-term child well-being outcomes (Yorke et al, 2018).…”
mentioning
confidence: 99%
“…FPS is the foundation upon which the resilience of children with ASD is built. Yorke, White, Weston, Rafia, Charman, and Simonoff, (2018) showed that resilient families are more likely to cope psychologically with the ASD condition of their children and are less likely to adopt negative behaviours towards children with ASD. Other researches affirm the strong relationship between dimensions of FPS such as clear routines, emotional sharing, and acceptance with children with ASD's adaptation (Schaaf et al, 2011;Ting & Weiss, 2017).…”
Section: The Role Of Family Socio-cultural Contexts In Developing Resmentioning
confidence: 99%
“…Including the child with ASD in activities at home can be stressful or chaotic (Yorke, et al, 2018), but the parents and family members should develop the resilience to work well with such children. On that note, frameworks should be developed to teach family members how to work with children with ASD in a bid to build their resilience.…”
Section: Best Practices For Developing Resilience In Children With Asdmentioning
confidence: 99%
“…L'ensemble de ces caractĂ©ristiques peut ĂȘtre associĂ© au stress parental (Pour une revue voir p.ex. Yorke et al, 2018). D'autres facteurs ; comme le « parcours du combattant » du diagnostic et des prises en charge, participent d'un amoindrissement du bien-ĂȘtre psychologique des parents d'enfants ayant un TSA, en particulier des mĂšres (Fourcade, Kruck, & RogĂ©, 2019).…”
Section: Introductionunclassified